Digitalization Strategy of the Dharma Usaha 'Maha' Women's Cooperative in Enhancing Member Entrepreneurship in Central Java Province - Yetty Yuliany Kusumaningrum; Abdul Aziz; Reni Nur Arifah (Institut Karya Mulia Bangsa, 2025)
This study aims to analyze the digitalization strategies implemented by the Dharma Usaha “Maha” Women’s Cooperative in enhancing the entrepreneurial capacity of its members in Central Java Province. Using a descriptive qualitative approach, the research explores the processes, utilization, and impact of digital technology on cooperative operations and member business development. Data were collected through preliminary analysis, document studies, and in-depth interviews to gain a comprehensive understanding of the implementation of digitalization strategies within the cooperative. The results indicate that digitalization strengthens the cooperative’s infrastructure through the provision of technological tools, development of integrated information systems, and digitization of administrative processes, thereby improving operational efficiency and transparency. Digitalization also provides broad access to information, digital training, and entrepreneurial literacy, contributing to enhanced skills, product innovation, and members’ readiness to face market competition. The use of social media and e-commerce platforms further expands marketing reach to regional and national levels. These findings underscore that digitalization strategies play a crucial role in building a technology-based entrepreneurial ecosystem that is inclusive and promotes women’s economic independence through cooperatives.